Genetic counselling and testing of adult patients with cardiomyopathies: insight from the EORP cardiomyopathy and myocarditis registry of the European Society of Cardiology. (25th November 2020) - Helio, T; Elliott, P; Koskenvuo, J.W; Gimeno, J.G; Tavazzi, L; Tendera, M; Kaski, P; Maggioni, A; Laroche, C; Caforio, A.L.P; Charron, P
Abstract: Introduction: Cardiomyopathies comprise a heterogeneous group of diseases, often of genetic origin. Purpose: We assessed the current practice of genetic counselling and testing of adult cardiomyopathy patients in the prospective ESC EORP cardiomyopathy registry. Methods: 3 208 adult patients from sixty-nine centres in 18 countries were enrolled. Clinical data on genetic counselling and testing and on the presentation of cardiomyopathies were gathered. Results: Genetic counselling was performed in 60.8% of all patients (75.4% in hypertrophic (HCM), 39.2% in dilated (DCM), 70.8% in arrhythmogenic right ventricular (ARVC) and 49.2% in restrictive cardiomyopathy (RCM), p<0.001). Comparing European geographical areas, genetic counselling was performed from 42.4% to 83.3% (p<0.001). It was provided by a cardiologist (85.3%), geneticist (15.1%), genetic counsellor (11.3%), or a nurse (7.5%), (p<0.001). Genetic testing was performed in 37.3% of all patients (48.8% in HCM, 18.6% in DCM, 55.6% % in ARVC and 43.6% in RCM, p<0.001). Index patients with genetic testing were younger at diagnosis, had more familial disease, family history of sudden cardiac death or implanted cardioverter defibrillators but less comorbidities than those not tested (p<0.001 for each comparison). At least 1 disease causing variant was found in 41.7% of index patients with genetic testing (43.3% in HCM, 33.3% in DCM, 51.4% in ARVC and 42.9% in RCM, p=0.13). Conclusion: We report on the practice of genetic counselling and testing in cardiomyopathies in Europe. Genetic counselling and testing were performed in a substantial proportion of patients but less often than recommended by European guidelines, and much less in DCM than in HCM and ARVC, despite evidence for genetic background. Funding Acknowledgement: Type of funding source: None